Immunohistochemical profile and molecular markers of lung carcinoma in tertiary care medical center - A retrospective observational study - Bhagiradhi Thimmapuram; Gokula Krishnan S; Praveen Raj S; Nalini Jayanthi Nagesh (Asian Journal of Medical Sciences, 2025)
Background: Lung carcinoma is one of the most prevalent malignancies globally, with high morbidity and mortality rates due to late-stage diagnosis and aggressive disease progression. Understanding immunohistochemical and molecular profiles is essential for improving diagnostic precision and guiding personalized therapy. Aims and Objective: This study aimed to evaluate the immunohistochemical profiles and molecular markers of lung carcinoma at a tertiary care center. Materials and Methods: This retrospective observational study included 67 patients diagnosed with lung carcinoma between June 2019 and June 2024. Data on patient demographics, histopathological subtypes, immunohistochemical markers (thyroid transcription factor-1 [TTF1], cytokeratin 7 [CK7], p63, and others), and molecular markers (epidermal growth factor receptor [EGFR], anaplastic lymphoma kinase [ALK], and ROS1) were analyzed. Statistical analyses were performed using SPSS v26. Results: Non-small-cell lung carcinoma (NSCLC) adenocarcinoma was the predominant subtype (85.1%), followed by squamous cell carcinoma (11.9%). TTF1 and CK7 were positive in 82.1% and 40.3% of cases, respectively, whereas p63 was positive in 17.9%, primarily in squamous carcinoma. EGFR mutations were detected in 52.5% of cases, highlighting their therapeutic relevance. ALK and ROS1 rearrangements were absent in all the tested cases. Conclusion: This study emphasizes the predominance of NSCLC adenocarcinoma and the diagnostic importance of TTF1 and CK7 expression. Molecular profiling is critical for the effective management of lung cancer with targeted therapies.